Program Sarasehan “Radikalisme Agama, Menyikapi Kebangkitan Taliban dan Kasus-Kasus Penistaan Agama” bagi Pemuda GKJ Karangalit Salatiga - Rius Panji Prabowo; Alexander Christophorus Ariel Purbowo; Rendra Puja Saputra; Janiesha Kimberly Prasetyo; Rizki Amalia Yanuartha (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
The workshop program with the theme "Religious Radicalism, Responding to the Rise of the Taliban and Cases of Blasphemy of Religion" was created for the youth of the GKJ Karangalit church in Salatiga with the aim of helping youth expand their knowledge and learn about current events and religious issues in the world. especially from a Christian perspective. Through this program, students from the Satya Wacana Christian University Faculty of Social and Communication Sciences participate in preparing programs according to their fields of knowledge. Although the youth of GKJ Karangalit Salatiga are few in number, there is high enthusiasm to join the program and help prepare for the service. From the results of this Community Service, it resulted in an increase in the knowledge capacity of the youth of GKJ Karangalit in the dangers of religious radicalism.